Aquisição da língua de sinais através de jogos e brincadeiras - Pinto, Milena Maria (Universidade Federal de São Carlos, 2018)
This research aims to understand the process of sign language development by deaf children through play and games in early childhood education. The research will use video recordings made over a period of six months in order to analyze children at play. The interaction between the children, the way and when they use sign language to communicate, the presence of language during play, and the way the teacher conducts the activities will be observed. The participants are children from Early Childhood Education, a public school in the interior of São Paulo, which has a Bilingual Education Program for the deaf, whose proposal is to provide Brazilian Sign Language – Libras as their first language throughout their school career. The interest in the topic arises from the realization of the importance of language in human development and, specifically, in the acquisition of language by deaf children. It is extremely important for deaf people to have the opportunity, from an early age, to have contact with sign language, just as hearing people have with the Portuguese language. Play was a reference aspect in the research because it is the basis of children's activities, learning and first school contacts. The episodes of interest were selected, cut out and transcribed; the analyses and discussions of the results are supported by Vygotsky's assumptions, as well as by authors in the field of deafness. The results indicate that when play occurs more naturally and according to the children's wishes, the language also emerges in a more natural and fluid way, without configuring a "class" in Libras. The data also point to the need for reflection on pedagogical practices that are more appropriate for the proposed age group, as well as the development of a curriculum for the development of Libras.
Acquisition of sign language through games and play
Keywords: Educação especial; Contexto bilíngue; Surdez; Brincar; Libras; Special education; Bilingual context; Deafness; Play; Libras; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO